(untitled) (Annals of Medical Research, 2021)
Aim: This research study was carried out as a descriptive study to determine the risk of postoperative constipation in liver transplant patients.Material and Methods: The study was conducted between September 2018 and November 2018 in the Liver Transplant Clinics of Liver Transplant Institute at İnönü University. The research population was composed of all of the adult patients who underwent surgery in these clinics. The sample of the study consisted of 95 patients who were selected from among these patients by using the non-random sampling method, who were able to communicate and volunteered to participate in the study. The data were collected through the face-to-face interview method using the Patient Information Form and the Constipation Risk Assessment Scale. Counts, percentages, mean scores, standard deviations, Kruskal-Wallis variance analyses, and independent samples t-tests were used to analyze data.Results: TOf the patents participating in the study, 65.3% were found to be in the moderate-risk group in terms of the development of constipation. Total CRAS score was found to be 12.15±3.06 (moderate risk). The risk of constipation was found to be significantly higher in patients who were aged 18–34, male, and high school graduates. Conclusion: More than half of the liver transplant patients who participated in the study were found to be at moderate risk for the development of postoperative constipation.